Effect of gold nanoparticle on photon upconversion based on sensitized triplet–triplet annihilation in polymer films. (2nd September 2017) - Yonemura, Hiroaki; Naka, Yuji; Nishino, Mitsuhiro; Sakaguchi, Hiroshi; Yamada, Sunao
ABSTRACT: Effect of gold nanoparticle (AuNP) on photon upconversion based on sensitized triplet-triplet annihilation (PUC-TTA) were examined in the system of platinum(II) octaethylporphyrin (PtOEP) and 9, 10-diphenylanthracene (DPA), when AuNPs were incorporated into polymer thin films containing PtOEP and DPA. The enhancements of the upconversion fluorescence from DPA and the phosphorescence of PtOEP were observed in the presence of AuNP. The enhancements were varied with AuNP loading and the maximum of enhancements was obtained at the AuNP loading (3.0%). The enhancements of PUC-TTA are most likely attributable to large electric fields due to localized surface plasmon resonance of AuNP.